Changes in peripapillary retinal nerve fiber layer thickness in chronic glaucoma and non-glaucoma patients after phacoemulsification cataract surgery (Medical Journal of Indonesia, 2015)
Background: Phacoemulsification is a common cataract operation nowadays. During phacoemulsification, variation in intraocular pressure (IOP) may occur, which might change the retinal nerve fiber layer (RNFL) thickness. This study was aimed to evaluate the change in peripapillary RNFL thickness and mean deviation (MD) of visual field after phacoemulsification in chronic primary glaucoma and non-glaucoma patients. Methods: Cohort prospective study was done on 26 patients (13 chronic glaucoma eyes and 13 non-glaucoma eyes) who underwent phacoemulsification. The changes in peripapillary RNFL thickness and MD of visual field were measured as the primary outcome. Comparison between pre- and post-surgery was analyzed with paired t-test, while unpaired t-test was used for comparison between groups. Results: There were no significant changes in RNFL thickness on both groups. Average RNFL thickness in glaucoma group before and after phacoemulsification were 94.9±20.0 μm and 99.1±21.3 μm, respectively (p>0.05). Average RNFL thickness in non-glaucoma group were 100.2±11.1 μm and 101.7±6.8 μm, respectively (p>0.05). Glaucoma patients yielded decreasing mean deviation (MD) of visual field, but it was not statistically significant (p=0.071). In contrast, the MD of visual field after surgery was significantly increased in non-glaucoma group (p=0.005). Conclusion: Phacoemulsification tended to increase peripapillary RNFL thickness in glaucoma or non-glaucoma patients. The visual field tended to decrease in glaucoma patients, but was significantly increased in non-glaucoma patients.